Improvements in spatiotemporal outcomes, but not in recruitment of automatic postural responses, are correlated with improved step quality following perturbation-based balance training in chronic stroke - Staring, Wouter H. A.; van Duijnhoven, Hanneke J. R.; Roelofs, Jolanda M. B.; Zandvliet, Sarah; den Boer, Jasper; Lem, Frits C.; Geurts, Alexander C. H.; Weerdesteyn, Vivian (Frontiers in Sports and Active Living, 2022)
Introduction: People with stroke often exhibit balance impairments, even in the chronic phase. Perturbation-based balance training (PBT) is a therapy that has yielded promising results in healthy elderly and several patient populations. Here, we present a threefold approach showing changes in people with chronic stroke after PBT on the level of recruitment of automatic postural responses (APR), step parameters and step quality. In addition, we provide insight into possible correlations across these outcomes and their changes after PBT. Methods: We performed a complementary analysis of a recent PBT study. Participants received a 5-week PBT on the Radboud Fall simulator. During pre- and post-intervention assessments participants were exposed to platform translations in forward and backward directions. We performed electromyography of lower leg muscles to identify changes in APR recruitment. In addition, 3D kinematic data of stepping behavior was collected. We determined pre-post changes in muscle onset, magnitude and modulation of recruitment, step characteristics, and step quality. Subsequently, we determined whether improvements in step or muscle characteristics were correlated with improved step quality. Results: We observed a faster gastrocnemius muscle onset in the stance and stepping leg during backward stepping. During forward stepping we found a trend towards a faster tibialis anterior muscle onset in the stepping leg. We observed no changes in modulation or magnitude of muscle recruitment. Leg angles improved by 2.3° in forward stepping and 2.5° in backward stepping. The improvement in leg angle during forward stepping was accompanied by a -4.1°change in trunk angle, indicating a more upright position. Step length, duration and velocity improved in both directions. Changes in spatiotemporal characteristics were strongly correlated with improvements in leg angle, but no significant correlations were observed of muscle onset or recruitment with leg or trunk angle. Conclusion: PBT leads to a multi-factorial improvement in onset of APR, spatiotemporal characteristics of stepping, and reactive step quality in people with chronic stroke. However current changes in APR onset were not correlated with the observed improvement in step quality. Therefore, we suggest that, in addition to spatiotemporal outcomes, other characteristics of muscle recruitment during a reactive step may improve after PBT.